Efektivitas Rotasi Pemberian Cacing Sutra Kering (Tubifex sp.) dan Pakan Komersil terhadap Pertumbuhan Ikan Mas (Cyprinus carpio) - Mangge, Permatasari Fibria Kero; Dahoklory, Nicodemus; Linggi, Yulianus (Jurnal Aquatik, 2025)
Goldfish (Cyprinus carpio) as a high-economic aquaculture commodity requires appropriate cultivation techniques to meet market demand. Feed management as the main key to successful cultivation remains a problem for farmers, including goldfish farmers. The use of commercial feed requires quite high costs so that farmers use alternative feed to increase the protein content of the feed. Silkworms (Tubifex sp.) are known as a natural feed that is widely used because they are high in protein and economical. This study aims to determine the effect of the rotation of natural feed silkworms (Tubifex sp.) and commercial feed (pellets). The research design used was a Completely Randomized Design (CRD) with 4 different treatments, namely, A (Pellet 30 days-silkworms the next 30 days), B (silkworms 30 days - pellets the next 30 days), C (Silkworms 60 days), D (Pellet 60 days) with a treatment duration of 2 periods of 60 days. The data obtained were analyzed using the LSD test. The best treatment from the research results was obtained in treatment D (60-day pellets) with absolute weight growth (2.53 gr) and the highest survival rate was obtained in treatment C (60-day silk worm feed), namely 93.3%.